Programa de capacitação para diretores de escolas públicas municipais de Uberaba: contribuições para a educação continuada - Santos Neto, Vicente Batista dos (2004)
This research studies the roles performed by the Principal at municipal schools from Uberaba and suggests guidelines for a Capability Program for School Principais. It’s a qualitative research developed after the case study method. The main research sources used were semi-structured interviews, documental analysis and bibliographic research. The theoretical line followed was divided into four parts, which are: 1) Studies about School Administration; 2) Legislative aspects about Education in Brazil and in Uberaba; 3) Continued Education of the School Principal; 4) Development and Training Programs. I interviewed eight out of the fourteen Principais elected by the school community and given possession from the year 2004 to 2007. After the researched literature and the analyses of the data obtained through the interviews, it was possible to detect the following aspects: the Principais’ roles are basically administrative, in accordance to the municipal legislation; the Principais show an initial education background based on Pedagogy and School Administration; their knowledge in the administration field are limited; the occurrence of the democratic management in practice is beneath the rules of legislation and the theoretical speeches; the democratic management would be promoted, in short, by the Principal and School Collegiate election; even though the School Administration course is required to take over the post, it little contributes to the PrincipaPs better performance in his/her administrative roles. Conceming these situations, some guidelines are presented for a Capability Program, based on Bohlander (2003) and Milkovich (2000) Training and Development theories, having as general outlines the performance of training necessities survey, administration knowledge insertion and training specific methodology for the person in charge of the management post.